E-Commerce Web Application Untuk Membantu Masyarakat - palit, juliana; Satria, Rizky Adi; Tantowi, Ahmad Ahyani (Jurnal Pengembangan Sistem Informasi dan Informatika, 2024)
Technological developments are currently developing very rapidly and can be utilized by business people. Using the right technology can improve performance in a company. Processes in the business sector are long, complicated and require a long time to become more efficient and reduce costs. E-commerce is a technology that can be applied to a company. E-commerce as an answer to the demands of globalization. With the number of internet users growing rapidly, this is the reason companies implement e-commerce. The development of e-commerce users in Indonesia is currently increasing due to the Covid-19 pandemic and Omicron has become an alternative for carrying out transactions between buyers and sellers to stabilize the economy. In implementing e-commerce to help people sell their products through an e-commerce website.Keywords—E-commerce; sistem informasi; jual-beli; produk; website